(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Olishkevych S. V. Early Character Education Programs in American Schools and their peculiarities. The article analyses major trends in education and society in XX century and their influence on character education in the USA, distinguishes two pioneer programs ‘Тhe Young Men’s Christian Association’ (The YMCA, The Boy Scouts of America’ (Тhe BSA) that first started doing character education in America, highlighted the way of these programs’ development before they managed to become part of American public school and school curricular.